Vaccines against poverty - MacLennan, Calman A. (National Academy of Sciences, 2014)
With the 2010s declared the Decade of Vaccines, and Millennium Development Goals 4 and 5 focused on reducing diseases that are potentially vaccine preventable, now is an exciting time for vaccines against poverty, that is, vaccines against diseases that disproportionately affect low- and middle-income countries (LMICs). The Global Burden of Disease Study 2010 has helped better understand which vaccines are most needed. In 2012, US$1.3 billion was spent on research and development for new vaccines for neglected infectious diseases. However, the majority of this went to three diseases: HIV/AIDS, malaria, and tuberculosis, and not neglected diseases. Much of it went to basic research rather than development, with an ongoing decline in funding for product development partnerships. Further investment in vaccines against diarrheal diseases, hepatitis C, and group A Streptococcus could lead to a major health impact in LMICs, along with vaccines to prevent sepsis, particularly among mothers and neonates. The Advanced Market Commitment strategy of the Global Alliance for Vaccines and Immunisation (GAVI) Alliance is helping to implement vaccines against rotavirus and pneumococcus in LMICs, and the roll out of the MenAfriVac meningococcal A vaccine in the African Meningitis Belt represents a paradigm shift in vaccines against poverty: the development of a vaccine primarily targeted at LMICs. Global health vaccine institutes and increasing capacity of vaccine manufacturers in emerging economies are helping drive forward new vaccines for LMICs. Above all, partnership is needed between those developing and manufacturing LMIC vaccines and the scientists, health care professionals, and policy makers in LMICs where such vaccines will be implemented.